PERBANDINGAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA SMA YANG DIAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DENGAN MODEL PROBLEM BASED INSTRUCTION - Amri, Amri (Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar, 2015)
This research was conducted in SMA Negeri 1 Baraka which employed two kinds of group experiment, namely experiment group I was taught by using cooperative learning GI model and experiment group II was taught by using PBI model. Research instruments were in the form of questionnaire to measure studentsâ learning motivation, test of biology learning outcomes to measure studentsâ ability before of after the learning process. The result shows that: (1) there is significant difference of motivation and biology learning outcomes between students who are taught using cooperative learning of group investigation (GI) model and problem based instruction (PBI) model at X grade students of SMA Negeri Baraka, where students who were taught by using GI model are highly motivated and have higher learning outcomes than students who were taught by using PBI model. (2) there is correlation between motivation and biology learning outcomes of students who are taught using cooperative learning of GI model by significant of correlation 0,786 classified on fair interpretation and PBI model by significant of correlation 0,838 classified on hight interpretation. Therefore, it is indicating that correlation between motivation and biology learning outcomes of students who are taught using cooperative learning of PBI model is higher than GI model.